SISTEM INFORMASI KURSUS MOBIL SATRIA JAYANTI BERBASIS WEBSITE - Riyanto, Harjo; Rahmatullah A.R, Syaifur (LPPM Universitas Bina Bangsa, 2023)
Satria Jayanti Driving Course is a driving school that has several branches in Jakarta with a considerable number of students. However, in its business processes, payment recording and payment reporting are still done using notebooks without any computerization. The frequent challenges faced by Satria Jayanti Driving Course are the manual payment management process, which often leads to errors in recording both student names and payment amounts, and the inefficient storage of payment receipts because they take up a lot of space. Payment data is often difficult to find when searching for old student payment records. Monthly transaction report creation becomes slow because previous transactions have to be reviewed again. If this continues, the inefficient business process will make customers feel uncomfortable. Therefore, to address the above issues, Satria Jayanti Driving Course needs a payment information system that can manage payments effectively. In this case, the author suggests developing a web-based payment information system using the PHP programming language, MySQL database, and a system development method with Rapid Application Development (RAD).